CPS1 augments hepatic glucagon response through CaMKII/FOXO1 pathway - Sun, Xiao-Meng; Wu, Xin; Wei, Meng-Guang; Zhu, Li-Zeng; Wu, Wen-hui; Zhou, Xin-Yue; Qi, Lian-Wen; Liu, Qun (Frontiers in Pharmacology, 2024)
Elevated glucagon levels are a characteristic feature of type 2 diabetes. This abnormal increase in glucagon can lead to an accelerated rate of gluconeogenesis. Glucagon also stimulates hepatic metabolism of amino acids, particularly promoting the formation of urea. The specific role of carbamoyl phosphate synthetase 1 (CPS1), a rate-limiting enzyme in the urea cycle, in the development versus the persistence of glucagon-induced hyperglycemia has not been previously established. Here, we reported that knockdown of CPS1 significantly reduces the glucagon response both in vivo and in vitro. Conversely, overexpression of CPS1 results in an overactive hepatic gluconeogenic response. Mechanistically, CPS1 induced the release of calcium ions from the endoplasmic reticulum, which in turn triggers the phosphorylation of CaMKII.The activation of CaMKII then facilitates the dephosphorylation and nuclear translocation of FOXO1, culminating in the enhancement of hepatic gluconeogenesis.Furthermore, the research discovers cynarin screened by in silico strategy, a natural CPS1 inhibitor derived from the artichoke plant, has the capacity to attenuate the hepatic glucagon response in a CPS1-dependent manner. Our findings suggests that CPS1 plays a pivotal role in mediating glucagon-induced hepatic gluconeogenesis, and cynarin, perform functions by repressing CPS1, may hold potential as a therapeutic agent for the treatment of diabetes.